‘My Roman Empire’: From Flashmob to Idiomatic Expression - E. V. Leontyeva (Научный диалог)
The semantic and historical analysis of the expression ‘moya Rimskaya imperiya’ [‘my Roman Empire’] is relevant in the context of neologism studies. The novelty of the research lies in the unique opportunity to observe the real-time formation of a linguistic unit in live communication. It is reported that in 2023, expressions formatted as elaborate sentences containing the stable construction ‘moya Rimskaya imperiya’ [‘my Roman Empire’] gained popularity in the Russian-speaking segment of youth internet communication, signifying ‘the subject of my constant memories, reflections, experiences, and thoughts’. The article reconstructs the history of the expression’s emergence, emphasizing that it cannot be considered a result of calquing since there was no situation of translating a linguistic unit from another linguistic-cultural context. The origin of the expression stems from a survey conducted by a blogger from Sweden, which spontaneously evolved into a flashmob format among internet users. The internationalization of the experiment led to the emergence of an experimental narrative in Russian linguistic culture, rather than individual words or phrases. The stages of transforming the verbal part of the experimental communication narrative into a stable expression are outlined. It is argued that due to the openness of the internet space and blogosphere, a new phenomenon of calquing emerges — calquing of the entire process of idiomatic expression formation, not just its form or meaning.